2019
DOI: 10.1111/pbi.13168
|View full text |Cite
|
Sign up to set email alerts
|

High‐efficient and precise base editing of C•G to T•A in the allotetraploid cotton (Gossypium hirsutum) genome using a modified CRISPR/Cas9 system

Abstract: SummaryThe base‐editing technique using CRISPR/nCas9 (Cas9 nickase) or dCas9 (deactivated Cas9) fused with cytidine deaminase is a powerful tool to create point mutations. In this study, a novel G. hirsutum‐Base Editor 3 (GhBE3) base‐editing system has been developed to create single‐base mutations in the allotetraploid genome of cotton (Gossypium hirsutum). A cytidine deaminase sequence (APOBEC) fused with nCas9 and uracil glycosylase inhibitor (UGI) was inserted into our CRISPR/Cas9 plasmid (pRGEB32‐GhU6.7).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(86 citation statements)
references
References 40 publications
3
77
0
1
Order By: Relevance
“…The base-editing approach using CRISPR/nCas9 (Cas9 nickase) or dCas9 (deactivated Cas9) fused with cytidine deaminase is a powerful tool to create point mutations. In this study, we point out the remarkable G. hirsutum-base editor 3 (GhBE3) base enhancing system developed to create single base mutations in the allotetraploid genome of cotton (Gossypium hirsutum) [101].…”
Section: Mutagens For Molecular Breedingmentioning
confidence: 99%
“…The base-editing approach using CRISPR/nCas9 (Cas9 nickase) or dCas9 (deactivated Cas9) fused with cytidine deaminase is a powerful tool to create point mutations. In this study, we point out the remarkable G. hirsutum-base editor 3 (GhBE3) base enhancing system developed to create single base mutations in the allotetraploid genome of cotton (Gossypium hirsutum) [101].…”
Section: Mutagens For Molecular Breedingmentioning
confidence: 99%
“…With the development of modern technologies, plant breeders have the opportunity to overcome this bottleneck. Studies have demonstrated that targeted mutagenesis and precise base editing can be accurately applied for the G. hirsutum genome using genome editing systems [68][69][70][71][72][73][74][75][76][77]. Genome resequencing has identified many domestication genes associated with fiber quality and yield traits.…”
Section: Box 2 a Model For Genetic Breakdown Of Interspecific Hybridmentioning
confidence: 99%
“…Cytosine base editor (CBE), the first member in the base editing toolbox, can convert cytidine (C) to thymidine (T) (or G to A) at specific genomic sites in an sgRNA‐dependent manner (Komor et al ., ). The most commonly used CBEs in plants consist of a Cas9 nickase (nSpCas9 (D10A)) fused with a cytidine deaminase and a uracil glycosylase inhibitor (UGI) (Li et al ., ; Lu and Zhu, ; Qin et al ., ; Shimatani et al ., ; Zong et al ., ). Although the CBEs have been shown to be functional in many plant species, the narrow target range and low editing efficiency considerably limit their application in crop breeding.…”
Section: Introductionmentioning
confidence: 98%